Daytime sleepiness is associated with altered resting thalamocortical connectivity. Issue 13 (9th September 2015) - Killgore, William D.S.; Vanuk, John R.; Knight, Sara A.; Markowski, Sarah M.; Pisner, Derek; Shane, Bradley; Fridman, Andrew; Alkozei, Anna
<x xml:space="preserve">Abstract</x> Thalamocortical connectivity is believed to underlie basic alertness, motor, sensory information processing, and attention processes. This connectivity appears to be disrupted by total sleep deprivation, but it is not known whether it is affected by normal variations in general daytime sleepiness in nonsleep deprived persons. Healthy adult participants completed the Epworth Sleepiness Scale and underwent resting-state functional MRI. Functional connectivity between the thalamus and other regions of the cortex was examined and correlated with Epworth Sleepiness Scale scores. Greater sleepiness was associated with inverse (i.e. lower or more negative) connectivity between the bilateral thalamus and cortical regions involved in somatosensory and motor functions, potentially reflecting the disengagement of sensory and motor processing from the stream of consciousness.